Antimicrobial activity of doubly-stapled alanine/lysine-based peptides. Issue 18 (15th September 2015) - Dinh, Thuy T.T.; Kim, Do-Hee; Luong, Huy X.; Lee, Bong-Jin; Kim, Young-Woo
Graphical abstract: Abstract: In this study, we examined the potential of Verdine's double-stapling system for the de novo design of amphipathic helical antimicrobial peptides. We designed, synthesized, and tested a prototypical doubly-stapled helix of an alanine/lysine based model sequence, which showed reasonable antimicrobial activities and highly increased proteolytic stability. We then show that its hemolytic activity as well as antimicrobial activities can be further manipulated through the systematic modifications. Overall, the preliminary results obtained from this study imply that the doubly-stapled helices of short peptides can serve as a highly promising scaffold for the rational design of potent, selective, and metabolically stable antimicrobial peptides that can combat against the growing problems of antibiotic-resistance.